2016
DOI: 10.1111/jocn.13163
|View full text |Cite
|
Sign up to set email alerts
|

Moments of joy and delight: the meaning of traditional food in dementia care

Abstract: This study provides insight into culture-sensitive dietary needs of institutionalised patients with dementia. The cultural significance of food for feeling contentment and social and physical well-being is discussed. Besides helping to avoid undernutrition, being served traditional dishes may be very important to reminiscence, joy, thriving and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…In our study, the participants emphasised the importance of having access to Sami food, and this could be related to culture, identity and heritage, because traditional food can represent a core element in this context . Hanssen and Kuven found that traditional foods can create feelings of belonging and joy in older people with severe dementia, some with a Sami background. Familiar tastes can awaken pleasant memories and boost patients’ sense of well‐being, identity and belonging .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our study, the participants emphasised the importance of having access to Sami food, and this could be related to culture, identity and heritage, because traditional food can represent a core element in this context . Hanssen and Kuven found that traditional foods can create feelings of belonging and joy in older people with severe dementia, some with a Sami background. Familiar tastes can awaken pleasant memories and boost patients’ sense of well‐being, identity and belonging .…”
Section: Discussionmentioning
confidence: 82%
“…Hanssen and Kuven found that traditional foods can create feelings of belonging and joy in older people with severe dementia, some with a Sami background. Familiar tastes can awaken pleasant memories and boost patients’ sense of well‐being, identity and belonging . The participants in our study highlighted the importance of Sami foods, and they wanted assistance from family or care providers in order to access and prepare Sami food when they no longer could do this themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based strategies to improve food choice and intake include offering a variety of foods buffet-style or family-style (Altus, Engelman, & Mathews, 2002;Douglas & Lawrence, 2015), where residents can select foods from a buffet or from the table where they are seated. In addition, serving familiar foods is important for people living with dementia (Gould & Basta, 2013;Hanssen & Kuven, 2016;Son, Therrien, & Whall, 2002), and this contrasted with Connie's experiences.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study on South Asian immigrants in the UK, it was reported that food and dieting also had religious meanings, as different religions have restrictions regarding what kind of food is allowed and not allowed (Rauf, (2011). Another study conducted in Norway on the Sami population, indigenous people of Northern Scandinavia, showed that when being served Sami food, the Sami patients with dementia appetite and nutritional intake improved, as well as that traditional food brought joy and a sense of belonging (Hanssen, 2013;Hanssen & Moene Kuven, 2015). As such, cultural food preferences need to be considered when providing care for immigrant persons with dementia.…”
Section: Introductionmentioning
confidence: 99%